2019
DOI: 10.1080/2162402x.2019.1652539
|View full text |Cite
|
Sign up to set email alerts
|

A poly-neoantigen DNA vaccine synergizes with PD-1 blockade to induce T cell-mediated tumor control

Abstract: The combination of immune-stimulating strategies has the potency to improve immunotherapy of cancer. Vaccination against neoepitopes derived from patient tumor material can generate tumorspecific T cell immunity, which could reinforce the efficacy of checkpoint inhibitor therapies such as anti-PD-1 treatment. DNA vaccination is a versatile platform that allows the inclusion of multiple neoantigencoding sequences in a single formulation and therefore represents an ideal platform for neoantigen vaccination. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 50 publications
(62 reference statements)
1
44
0
Order By: Relevance
“…Furthermore, the results of flow cytometry showed that the vaccine increased the proportion of CD4+ T and CD8+ T cells in the spleen and TME, suggesting the important role of CD4+ T and CD8+ T cells in antitumor immunity. Consistent with our results, Tondini et al and Tian et al evaluated CD4+ T and CD8+ T cells in vivo by injecting anti-CD4 and anti-CD8 antibodies in mice, and found that tumor regression was dependent on CD4+ T and CD8+ T cells [ 25 , 26 , 27 ]. Other experiments have also shown that increases in the numbers of CD4+ T and CD8+ T cells in the TME are closely related to tumor prognosis [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the results of flow cytometry showed that the vaccine increased the proportion of CD4+ T and CD8+ T cells in the spleen and TME, suggesting the important role of CD4+ T and CD8+ T cells in antitumor immunity. Consistent with our results, Tondini et al and Tian et al evaluated CD4+ T and CD8+ T cells in vivo by injecting anti-CD4 and anti-CD8 antibodies in mice, and found that tumor regression was dependent on CD4+ T and CD8+ T cells [ 25 , 26 , 27 ]. Other experiments have also shown that increases in the numbers of CD4+ T and CD8+ T cells in the TME are closely related to tumor prognosis [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the previously described Adpgk epitope is beyond doubt relevant for vaccination-induced MC-38 tumor control as is observed by several groups, 28,32,33 including our own experimental data with specific DNA vaccination. 34 In addition, care should be taken with the origin of the MC-38 cell line, as different lines may contain other neo-epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…DNA vaccine induces Cytotoxicity of CD8 T cells. A single dose of DNA vaccine combined with anti-PD-1 treatment significantly delays tumor growth in tumor-bearing mice inoculated with MC38 colon cancer cell line and some of the tumors are cleared completely, with a cure rate of 25%, and this indicates that tumor vaccine works synergistically with immune checkpoint blocking therapy (28).…”
Section: Combination Of Cancer Vaccine With Pd-1/pd-l1 Inhibitorsmentioning
confidence: 93%